2020
DOI: 10.18510/hssr.2020.8421
|View full text |Cite
|
Sign up to set email alerts
|

Do Time Management Factors Impede Students’ Academic Achievement? : A Casestudy – Sohar University, Oman

Abstract: Purpose: The objective of the research study is to critically analyze the factors impeding time management towards students’ academic performance achievement. Design/methodology/approach: The study was carried out using a well-defined questionnaire collecting samples from 164 undergraduate students studying in the Faculty of Business, Sohar University, Sultanate of Oman from a population of 700 undergraduate students. For the study, the cluster-sampling method was adopted. SPSS was used to perform the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This finding was agreed with the present study, which showed that there were no statistical significant differences between the studied groups achieving different academic performance (GPA) regarding academic problems related to organization, equipment and library (Table 3) (P= 0.5, 0.7, 0.4 respectively). However, these findings were not matched with a cross-sectional survey targeted 562 students in Sohar University in Oman, revealed that there is a significant relationship between institution environments and student's performance (P=0.000) ) (18) .This can be explained by the fact that most of the students participating in the study unanimously agreed that despite the weakness of the college's resources, they are distributed equitably to all students regardless of their academic performance.…”
Section: College Of Nursing and Minia Universitymentioning
confidence: 72%
“…This finding was agreed with the present study, which showed that there were no statistical significant differences between the studied groups achieving different academic performance (GPA) regarding academic problems related to organization, equipment and library (Table 3) (P= 0.5, 0.7, 0.4 respectively). However, these findings were not matched with a cross-sectional survey targeted 562 students in Sohar University in Oman, revealed that there is a significant relationship between institution environments and student's performance (P=0.000) ) (18) .This can be explained by the fact that most of the students participating in the study unanimously agreed that despite the weakness of the college's resources, they are distributed equitably to all students regardless of their academic performance.…”
Section: College Of Nursing and Minia Universitymentioning
confidence: 72%
“…Based on the CGSS2006 data, Gu et al (2022) found that families with complete families have a more complete investment structure for their children, and parents are more willing to invest in their children, while single-parent families rely more on grandparents to care for and invest in their children. Alani & Hawas (2021)found that the rural family environment and the marital status of parents can influence the learning environment of children, directly affecting their performance.…”
Section: Discussionmentioning
confidence: 99%
“…Contrasted with the study done Alani et al (2020) that critically analyzes the factors impeding time management towards students' academic performance achievement. The empirical findings in this study show that none of the claimed time management-related elements had an impact on students' academic achievement.…”
Section: Time Managementmentioning
confidence: 99%